2016
DOI: 10.1007/s00380-016-0802-5
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of epicardial fat thickness by transthoracic echocardiography for predicting high-risk coronary artery plaques

Abstract: Epicardial adipose tissue (EAT) volume is reported to be associated with coronary plaques. We evaluated whether non-invasive measurement of EAT thickness by echocardiography can predict high-risk coronary plaque characteristics determined independently by coronary computed tomography (CT) angiography. We enrolled 406 patients (mean age 63 years, 57 % male) referred for 64-slice CT. EAT was measured on the right ventricle free wall from a parasternal long-axis view at the end of systole. High-risk coronary plaq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 41 publications
0
10
0
2
Order By: Relevance
“…One study was excluded because it presented the association of EAT with plaque lipid percentage rather than specified numbers of patients with HRP . Seven studies reported CT assessment of HRP (n=3573) and 2 studies reported invasive assessment of HRP (n=199). Seven studies measured EAT‐v (n=3284), and 2 studies measured EAT‐t (n=488).…”
Section: Resultsmentioning
confidence: 99%
“…One study was excluded because it presented the association of EAT with plaque lipid percentage rather than specified numbers of patients with HRP . Seven studies reported CT assessment of HRP (n=3573) and 2 studies reported invasive assessment of HRP (n=199). Seven studies measured EAT‐v (n=3284), and 2 studies measured EAT‐t (n=488).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is also expensive and has higher time consumption during the procedure, giving it a significant disadvantage [ 132 , 133 ]. In this sense, Tachibana et al [ 134 ] have evaluated the predictive ability of transthoracic echocardiography to predict high-risk plaques, confirmed by coronary computed tomography angiography from epicardial fat thickness, with this being considered a good noninvasive predictor. Therefore, the use of echocardiography is the most cost-effective method today especially in regions where the availability of high cost imaging studies is low.…”
Section: Epicardial Fat: How To Quantify It?mentioning
confidence: 99%
“…One study was excluded because it presented the association of EAT with plaque lipid percentage rather than specified numbers of patients with HRP. 20 Seven studies reported CT assessment of HRP [21][22][23][24][25][26][27] (n=3573) and 2 studies reported invasive assessment of HRP 29,30 (n=199). Seven studies measured EAT-v 21-26,29,30 (n=3284), and 2 studies measured EAT-t 27,28 (n=488).…”
Section: Resultsmentioning
confidence: 99%